Prevalence of obesity among adolescents at secondary schools in Kirkuk city - Danok, abas; ghanem, eqbal (Iraqi National Journal of Nursing Specialties, 2013)
Objective: to identify the secondary school adolescent's obesity, and to find out the relationship betweenadolescents obesity characteristics and their family history.Methodology: A cross-sectional study was carried out among 537 adolescents (270 boys and 267 girls) aged 12-15years selected by means of a multistage stratified random sampling technique.Results: the prevalence of obesity among adolescents was 22.3%. (55.8%) of the obese adolescents were male,(42.5%) their age is (13) years old, and (79.2%) of them coming from middle level of socio economic status score.There are a significant relationship between obese adolescents and their family history of obesity which indicatedthat obese father, and obese brother /sister (0.000, 0.037, & 0.000) respectively have a highly significantrelationship with adolescents' obesity.Recommendation: Intervention programs focusing on promoting changes in lifestyles, food habits and increasingphysical activity need to be implemented at the earliest stage of children life